2010
DOI: 10.1021/ol100896n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (±)-Eusynstyelamide A

Abstract: The synthesis of (±)-eusynstyelamide A has been accomplished in six steps in 13% overall yield from 6-bromoindole, methyl glycidate, and Boc-protected agmatine. If oxygen is carefully excluded from the reaction, the key NaOH-catalyzed aldol dimerization of the α-ketoamide proceeded efficiently to give Boc-protected eusynstyelamide A.Tapiolas and co-workers recently reported the isolation of eusynstyelamides A (1), B (2), and C (3) from the Great Barrier Reef ascidian Eusynstyela latericius and assigned their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…1 The mode of action is not known, but the closely related dodecylguanidinium acetate ( 4 , dodine) has been in widespread use since 1956 as a fungicide and may act by membrane disruption. 3 As part of an ongoing program in the synthesis of structurally novel guanidine-containing natural products, 4 we planned to prepare phidianidines A ( 1a ) and B ( 1b ) by coupling of the appropriate ethyl indole-3-acetate ( 2a or 2b ) with hydroxyguanidine 3 containing a suitably protected nitrogen on the other end of the five carbon side chain. There is limited precedent for the synthesis of 3-amino-1,2,4-oxadiazoles by coupling of esters with hydroxyguanidines 5 and nature may use a related route for the biosynthesis of the phidianidines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 The mode of action is not known, but the closely related dodecylguanidinium acetate ( 4 , dodine) has been in widespread use since 1956 as a fungicide and may act by membrane disruption. 3 As part of an ongoing program in the synthesis of structurally novel guanidine-containing natural products, 4 we planned to prepare phidianidines A ( 1a ) and B ( 1b ) by coupling of the appropriate ethyl indole-3-acetate ( 2a or 2b ) with hydroxyguanidine 3 containing a suitably protected nitrogen on the other end of the five carbon side chain. There is limited precedent for the synthesis of 3-amino-1,2,4-oxadiazoles by coupling of esters with hydroxyguanidines 5 and nature may use a related route for the biosynthesis of the phidianidines.…”
mentioning
confidence: 99%
“…Eventually we found that reduction of the azide with activated zinc 10 and ammonium formate in MeOH for 7 h at 25 °C proceeded cleanly to give polar amine 12b that was used without purification. 11a Coupling of 12b with Boc-protected S -methylisothiourea 13 using Et 3 N and AgNO 3 4b, 12 in DMF for 2 h at 0 °C and 5 h at 25 °C afforded protected guanidine 14b in 60% yield from 11b . Deprotection of 14b by stirring in 10:1 CH 2 Cl 2 /TFA for 8 h at 25 °C removed the Boc protecting groups providing phidianidine B ( 1b ) in 92% yield.…”
mentioning
confidence: 99%
“…3 ), may originate from the condensation of two β‐ketoamides. This hypothesis was strengthened by Snider's et al “biomimetic” syntheses of anchinopeptolide D ( 1d ), and eusynstyelamide A ( 3 ) . In their seminal study, Minale et al also reported the isolation of cycloanchinopeptolide C ( 2c ), obviously formed by an intramolecular [2+2] cycloaddition from anchinopeptolide C ( 1c ).…”
Section: Introductionmentioning
confidence: 98%
“…This hypothesis was strengthened by Snider's et al "biomimetic" syntheses of anchinopeptolide D (1d), [6] and eusynstyelamide A (3). [7] In their seminal study, Minale et al also reported the isolation of cycloanchinopeptolide C (2c), [2] obviously formed by an intramolecular [2+2] cycloaddition from anchinopeptolide C (1c). Later, Snider et al could synthesize the non-natural cycloanchinopeptolide D (2d) thereby giving clues concerning the origin of the natural cycloanchinopeptolide C. Herein, we report our reinvestigation of the Mediterranean sponge Phorbas tenacior providing i-new insight into the stereocontrol in the biosynthesis of the central pyrrolidinone ring with the structure elucidation of the new anchinopeptolide E (1e) and ii-conclusions concerning the origin of cycloanchinopeptolide C (2c).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7]9,17 Typical oxidants employed for this oxidation are NaOCl, 5-10 dimethyldioxirane, 11 t-BuOOH with BuLi, 12,13 and H 2 O 2 with hetero-polyacid 14 or Mn 15 catalysts and NaHCO 3 as the activator. The appropriate choice of ammonium salts fitting to the polarity of the substrates and the reaction under slightly basic conditions were essential for efficient reactions.…”
mentioning
confidence: 99%